Detection, prevention and treatment of COVID‐19 and opportunities for nanobiotechnology. Issue 4 (15th March 2022) - Bao, Qing; Yang, Tao; Yang, Mingying; Mao, Chuanbin
Abstract: Since the outbreak of COVID‐19, the number of confirmed cases and deaths has increased globally at a dramatic speed. In view of the serious health threat to humans, this review discusses the state‐of‐the‐art studies about fighting this disease. It summarizes the current strategies and recent advances in detecting, preventing, and treating COVID‐19 and interprets the underlying mechanisms in detail. Detection of COVID‐19 can be successfully achieved by multiple techniques such as polymerase chain reaction, computed tomography imaging, and nano‐biosensing. Inactivated virus vaccine, nucleic acid vaccine, and different nanoparticles have been employed to effectively prevent COVID‐19. A variety of agents such as antiviral agents, neutralizing antibodies, and nanotherapeutics have been developed to treat COVID‐19 with exciting efficacy. Although nanobiotechnology has shown great potential in the diagnosis, prevention, and treatment of COVID‐19, efforts should be made to explore new biocompatible nano‐biomaterials to advance this field to clinical applications. Hence, nanobiotechnology paves a new way to detect, prevent, and treat COVID‐19 effectively. Abstract : Since the outbreak of COVD‐19, the number of confirmed cases and deaths has increased globally at a dramatic speed. In view of the serious health threat to humans, this review discusses the state‐of‐the‐art studies about fighting this disease. It summarizes the current strategies and recent advances in detecting, preventing, and treating COVID‐19 and interprets the underlying mechanisms in detail.